The Role Of National Land Agency In Acceleration Of Land Registration For Legal Certainty - Muhammad Yamin; Zaidar Zaidar; Zakiah Zakiah (Nagari Law Review, 2018)
Observing a lot of land conflicts in Indonesia which is constantly increasing, and followed by the rapidly growing populations that caused the demand for land will also increase automatically. While the number of the available land is limited (not increasing). This condition will surely causes problems on controlling and ownership of the land. This research aims to identify the factors which causes conflict (dispute) of land, by doing inventory to the lands which is owned by the community (whether it is registered or not registered). From this temporary research result, it is known that, the implementation of the land registration in Deli Serdang district (the research location) has not happened as expected. It can be seen from the number of land which has not been registered, this condition will certainly trigger conflicts or disputes in society, both ownership boundary disputes, control of illegal land (arable land), inheritance disputes, etc. Certificate ownership mostly only exist in urban area. The lack of interest by the community to join the land registration is due to various of reasons, which is: 1) the community do not recognized the purpose of land registration, 2) the cost is expensive, 3) the management is convoluted, 4) the community feels that it is not a necessary to do it, 5) arable land. In this research, the role of National Land Agency (NLA) as the organizer of land registration has not been surely prominent, it is visible that the NLA office is more passive, which is only waiting for the arrival of the owner land to register their lands, NLA should be more involved in land registration and followed by socialization, counseling for the community. As well for the land disputes which is in the region of the Land Office until this moment is currently unfinished and still having a lot of problems, in order to achieve the above purpose, Deli Serdang Land Office has taken steps by empowering all the existing abilities, it has been a huge duty for Land Office, by remembering there will be more and more usage and utilization in the future, while the available land is limited, and hoping that the community will be motivated to registered their lands for achieving the legal certainty.